Discovery and validation of biomarkers for Parkinson’s disease from human cerebrospinal fluid using mass spectrometry-based proteomics analysisResearch in context - Sungtaek Oh; Jaehun Jung; Jinhyeok Kim; Yura Jang; Catherine C. Bakker; Alexander Y. Pantelyat; Zhen Zhang; Ted M. Dawson; Chan Hyun Na; Liana S. Rosenthal (EBioMedicine)
Summary: Background: Proteomic biomarkers for Parkinson’s disease (PD) are critical for identifying new targets for disease-modifying therapies and expanding our understanding of disease pathophysiology. Methods: Deep proteome analysis of a cerebrospinal fluid (CSF) cohort (40 PD, 40 controls) coupled with previous data from the substantia nigra (SN) proteome was used to discover low abundance biomarkers involved in PD pathogenesis. We validated our findings using parallel reaction monitoring mass spectrometry with an independent cohort of CSF samples (80 PD, 80 controls). We further evaluated our biomarkers with a separate cohort of 80 individuals with Dementia with Lewy Bodies (DLB). We then correlated our candidate biomarkers with motor and cognitive performance. Findings: We identified 3683 unique proteins, 1425 of them quantified across all 80 discovery samples and 505 that separated PD from controls. Using a stepwise criterion and integrating with 1140 differentially expressed proteins in SN, we identified 34 candidate biomarker proteins. The validation study resulted in 8 proteins (VSTM2A, VGF, SCG2, PI16, OMD, FAM3C, EPHA4, and CCK) with expression patterns and effect sizes like the discovery set. When controlling for age and gender, CCK and OMD maintained their significance and two additional proteins trended toward significance (VGF and PI16, p = 0.057). PI16 and OMD were upregulated in PD, while the others were downregulated. Our investigation is the first to our knowledge to identify PI16 as a possible biomarker and to identify CCK in the CSF of individuals with PD. Combining 4 of the proteins had modest ability to separate PD from controls. CCK and VGF significantly predicted MoCA total scores amongst the DLB group. Interpretation: These candidate biomarkers add to our understanding of PD pathophysiology and the relationship between PD and DLB. They provide further research directions toward disease-modifying therapies. Funding: National Institute of Neurological Disorders and Stroke.